2016
DOI: 10.1007/s10668-016-9769-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of globalization on Ecological Footprints: an empirical analysis

Abstract: Whether globalization is sustainable is a contested issue. The quantitative literature on the Maastricht Globalization Index (MGI) and the KOF index of globalization shows that globalization contributes positively to economic and human development, environmental performance, mortality, gender equality and physical integrity rights. However, globalization also drives within-country income inequality, especially in developing countries. Evidence on the effects of globalization on the ecological environment does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(66 citation statements)
references
References 31 publications
4
61
1
Order By: Relevance
“…Several studies use this as an index for environmental degradation (Hassan, Xia, Khan, & Shah, 2019;Siche, Pereira, Agostinho, & Ortega, 2010) This index has the advantages of directly and indirectly demonstrating the environmental effects of production and consumption. It has been addressed in the literature in many aspects, the effect economic growth on the ecological Footprint (Aşıcı & Acar, 2016;Hassan, Baloch, Mahmood, & Zhang, 2019;Hassan, Xia, et al, 2019), the impact of FDI (Liu & Kim, 2018;Udemba, 2020;Zafar et al, 2019), socio-political factors (Charfeddine & Mrabet, 2017;S.-T. Chen & Chang, 2016;Dogan, Taspinar, & Gokmenoglu, 2019), and globalisation (Ahmed, Wang, Mahmood, Hafeez, & Ali, 2019;Figge, Oebels, & Offermans, 2017;Rudolph & Figge, 2017;Sabir & Gorus, 2019).…”
Section: Ecological Footprintmentioning
confidence: 99%
“…Several studies use this as an index for environmental degradation (Hassan, Xia, Khan, & Shah, 2019;Siche, Pereira, Agostinho, & Ortega, 2010) This index has the advantages of directly and indirectly demonstrating the environmental effects of production and consumption. It has been addressed in the literature in many aspects, the effect economic growth on the ecological Footprint (Aşıcı & Acar, 2016;Hassan, Baloch, Mahmood, & Zhang, 2019;Hassan, Xia, et al, 2019), the impact of FDI (Liu & Kim, 2018;Udemba, 2020;Zafar et al, 2019), socio-political factors (Charfeddine & Mrabet, 2017;S.-T. Chen & Chang, 2016;Dogan, Taspinar, & Gokmenoglu, 2019), and globalisation (Ahmed, Wang, Mahmood, Hafeez, & Ali, 2019;Figge, Oebels, & Offermans, 2017;Rudolph & Figge, 2017;Sabir & Gorus, 2019).…”
Section: Ecological Footprintmentioning
confidence: 99%
“…Goryakin et al (2015) demonstrated that social and political globalizations had the most profound positive association with women's propensity to be overweight and dominate the influence of economic and the overall index of globalization. Figge et al, (2017) investigated the effect of various measures of globalization on ecological footprints. The authors observe that the overall index of globalization significantly impacted on ecological footprints.…”
Section: Globalization and Sustainable Developmentmentioning
confidence: 99%
“…Lazarus, et al [41] illustrated that almost 35% of the carbon Footprint was embodied in international trade. Figge, et al [42] conclude that the overall index of globalization significantly increases the Ecological Footprint of consumption, exports, and imports. Gao and Tian [43] used the ecological trade deficit to assess the pressure created by the export and import of resources and products.…”
Section: Literature Reviewmentioning
confidence: 99%